Verbalisan Witness Position as Evidence of a Criminal Case - M. Kemal Pasha Zahrie (Ius Poenale, 2021)
The presence of Constitutional Court Decision Number 65/PUUVIII/2010 expands the meaning of witnesses in Article 1 point 26 of the KUHAP, resulting in the emergence of various interpretations in criminal justice practice concerning the position of verbal witness testimony as evidence. Juridically, the decision creates problems considering that the Criminal Procedure Code or Kitab Undang-Undang Hukum Acara Pidana (KUHAP) does not recognize verbal witnesses' testimony as evidence. This study examined the position and the strength of verbal witnesses' testimony as evidence in criminal proceedings. After gathering all the data using normative and empirical juridical research, this paper concludes that the testimony of verbal witnesses is grouped in the evidence of guidance in Article 188 Paragraph (1) of the KUHAP because the testimony of verbal witnesses is not primary evidence. After all, its existence is contingent on the judge's willingness to employ it. The strength of proof of testimony of verbal witnesses is that they must satisfy the elements of Article 188 paragraph (1) of the KUHAP, namely the information referred to in the form of events or circumstances concerning a criminal act, as well as conformity with other evidence, as required by Article 188 paragraph (2) of the KUHAP.